Crowd and crisis management - Vizconde, Angelie Marie; Magnaye, Alejandro ;Malabanan, Laila D. (Sta. Cruz, Manila : Edric Publishing House, 2022)
The tourism industry is considered as one of the fastest growing industries in the world.
Chapter 1. Defining Crisis Management -- Chapter 2. Phases in crisis management -- Chapter 3. Basics of Crisis Management -- Chapter 4. The Crisis Management Plan -- Chapter 5. Establishing a crisis management team and the role of the crisis management team -- Chapter 6. Putting Crisis Management into Action -- Chapter 7. Psychology of crisis management decision -- Chapter 8. Emergency response scenario, contingency plan and damage control -- Chapter 9. Common crisis management plan weaknesses -- Chapter 10. A crisis management checklist -- Chapter 11. Best Practices and Tips in Crisis Management.
Includes bibliographical references.
Keywords: CRISIS MANAGEMENT